Adaptive radar signal processing (John Wiley & Sons, 2006)
An Exploration of Key Issues Integral to the Design of Adaptive Radar Systems. This collaborative work presents the results of over twenty years of pioneering research by Professor Simon Haykin and his colleagues, dealing with the use of adaptive radar signal processing to account for the nonstationary nature of the environment.